THE AMERINDIAN AND THE MYTH OF THE GOLDEN AGE - Garcia, Alberto (Revista Literatura em Debate, 2013)
In discussing the influence of myth upon the initial moments of contact between Europeans and Amerindians, perhaps no other image is more predominant in this cultural exchange than Amerindian emerging as a being from the mythical Golden Age of mankind. The predominance of this myth in early encounters between the two cultures was a result of the renewed interest in antiquity and the classical themes contained within the canon of Greek and Roman works. In this essay, I examine several sources by which 15th century Europeans would have known of the Golden Age myth, (Hesiod’s epic poem Works and Days, Lucretius’s epic On the Nature of Things, and Ovid’s Metamorphoses) and then demonstrate how some of the common elements of this myth become manifest in short excerpts from the initial descriptions of the Amerindians provided by Christopher Columbus and Pero Vaz da Caminha. In drawing connections between the Golden Age myth and the writings of Columbus and Caminha, it is hoped that this small survey of the literature will demonstrate how myth enabled the European to describe foreign beings in a familiar imagery that extended from Western antiquity. O AMERÍNDIO E O MITO DA IDADE DO OURO Na discussão da influência do mito nos momentos iniciais do contato entre europeus e ameríndios, talvez nenhuma outra imagem seja tão relevante do que a do ameríndio como um ser da Idade do Ouro mítica. A predominância desse mito nos primeiros encontros entre as duas culturas foi o resultado de um renovado interesse na antiguidade e nos temas clássicos contidos no cânone das obras gregas e romanas. Neste ensaio, examino varias das fontes através das quais os europeus teriam ficado sabedores do mito da Idade do Ouro (o poema épico Os trabalhos e os dias, de Hesíodo, o poema épico A natureza das coisas, de Lucrecio, e Metamorfoses de Ovídio) e após demonstro como alguns dos elementos comuns desse mito se manifestaram através de pequenos excertos das descrições iniciais dos ameríndios dadas por Cristóvão Colombo e Pero Vaz de Caminha. Ao traçar conexões entre a Idade do Ouro e os escritos de Colombo e Caminha, espera-se demonstrar como o mito habilitou o europeu a descrever seres que lhe eram desconhecidos usando um imaginário familiar que datava da antiguidade clássica.